Three Identity Principles at the Core of Comparative Economic Development Management: Lessons for Emerging African Nations - Michel, Louicius (Journal of Comparative International Management, 2019)
The aim of this article is to investigate the role of national or social identity at different stages of the industrialized nations’ economic development models in order to draw some actionable lessons for emerging markets and developing African economies. The main assumption is that social identity is at the core of the economic management process industrialized nations implement with regard to achieving sustainable development goals. In order to detect actionable information with practical or methodological relevance, national identity was identified as the independent variable, and economic development as the dependent variable. Although the concept of identity is diversely defined in scholarly literature, it is commonly understood as the lens through which an individual perceives himself/herself or how a group of individuals perceive themselves, and their role in finding a way to cope with environmental challenges. Therefore, there is a double level of identity: at the individual level, and collectively as a nation. This identity is at the core of social reflexivity, which is used to envision, manage, and structure the institutional actions that are conducive to economic development. National and international development agencies have been experimenting with different models to achieve economic development in the emerging countries since the creation of the Bretton Woods Institutions at the end of the Second World War. The Millennium Development Goals (MDG) of the United Nations remain the last major multilateral management framework in a series of trial-and-errors over the last sixty years. Using an exploratory and descriptive approach, this article systematically compares the core of the economic development models of the Western nations and that of the newly emerging countries. The results of this analysis show that to achieve their economic development goals, industrialized and emerging countries built the managerial core of their development models on three major foundations: a political system that stems from their own idiosyncrasies, a belief system that comes from their own history and traditions, and a unique but non-exclusive mode of production and resource allocation. These three pillars form a tryptic management principle of sustainable economic development ready for adaptation and adoption.